THE USE OF LYRICS FEATURE ON SPOTIFY TO IMPROVE STUDENTS’ LISTENING SKILL - Nadilla Laili Alfahri; Aswir (LPPM Universitas PGRI Jombang, 2024)
The aim of this study is to discover whether the use of the lyrics feature on Spotify improve students' listening abilities in learning English at SMPN 37 Jakarta. As a result, this study methodology is quantitative and uses a pre-experimental design. The sample was chosen from a seven-grade population of 288 students using cluster random sampling, with only one class, consists of 36 students. The data was acquired by a pre-test and post-test with one essay. The outcomes of this research analysis revealed that the average pre-test score was 38.33, while the average post-test score was 69.31. These results indicate that the pre-test and post-test data are regularly distributed. As a result, it is possible to conclude that Spotify's lyrics feature has an influence on improving students' listening skills.